Critical psychiatry: a brief overview. (17th December 2018) - Middleton, Hugh; Moncrieff, Joanna
SUMMARY: Critical psychiatry has often been confused with what is widely known as 'anti-psychiatry'. In this article the distinction is clarified and the particular contribution critical psychiatry makes is outlined. That contribution is constructive criticism: of the relationship between medicine and mental health practice, of the way drug and psychotherapeutic treatments for mental health difficulties might be better understood. These have implications for everyday clinical practice and there is much to be gained by openly embracing the controversies critical psychiatry highlights. LEARNING OBJECTIVES: Understand the origins of critical psychiatry and recognise some of the difficulties that arise from identifying psychiatry with medicine Appreciate the differences between disease-centred and drug-centred approaches to prescribing psychiatric medication Become aware of implications that arise from psychotherapeutic outcomes research DECLARATION OF INTERESTS: H. M. and J. M. are co-chairs of the UK Critical Psychiatry Network.